Representasi Kepemimpinan Karakter King Magnifico Film Wish (Analisis Semiotika Roland Barthes) - Haura Zahra Yoelianto; Vera Wijayanti Sutjipto (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study analyzes the representation of King Magnifico's leadership in the animated film Wish using Roland Barthes' semiotic approach. The film depicts Magnifico's transformation from a charismatic leader to an authoritarian and corrupt leader. A descriptive qualitative method was used by examining visual and narrative signs such as dialogue, costumes, colors, expressions, and symbols of power through Barthes' three levels of meaning, namely denotation, connotation, and myth. The results of the study show Magnifico's character change marked by strong visual attributes, ranging from changes in clothing colors to gestures and scene atmospheres that depict absolute power. Myth analysis reveals that the film legitimizes authoritarian leadership as something natural in social structures, while also criticizing domination without public dialogue. This study contributes to the study of character leadership representation in animated films and expands the application of Barthes' semiotic analysis in revealing the ideological meanings contained in film media.